GAMBARAN BATITA PENDERITA PNEUMONIA YANG DIRAWAT INAP DI RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2015 - jenika romian hutauruk; Sori Muda Sarumpaet; Rasmaliah . (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Abstract Pneumonia is one of health issues and the biggest contributor that causes of death for children under five years old. Pneumonia kills 1 in 5 children under five years old, kills more than 2 million children under five years old every year and mainly in developing countries. In 2013 at North Sumatra, there are 23.643 cases of pneumonia. This study aims to describe the the children under three years old with pneumonia who are hospitalized at Santa Elisabeth Hospital Medan in 2015. This study uses the case series and the population is all of the the children under three years old with pneumonia who are hospitalized at Santa Elizabeth Hospital in 2015, total population is 106 children and be the sampel. This study uses secondary data with statistical analysis Chi-Square test, Mann-Whitney test and Kruskal-Wallis tes. The result describe in narrative, in frequency distribution table, in pie and bar chart. This study showed that the proportion of the children under three years old with pneumonia is highest in the age group 24-35 months (44.3%), male (60.4%), Batak (93.4%), Protestants (75.5%), Medan (64.2%), good nutritional status (76.5%), incomplete immunization status (59.4%), without concomitant diseases (83.0%), the degree of pneumonia (91.5%) , average of treatment duration 4.76 days and recovered (83.0%). There is no difference in age with pneumonia based on the degree of pneumonia, average of treatment duration based on age, degree of pneumonia and after treatment conditions. There is a difference in average of treatment duration based on nutritional status and concomitant diseases, the nutritional status based on the degree of pneumonia and the degree of pneumonia based on after treatment conditions.Children's polyclinic of Santa Elisabeth Hospital provide a counseling for the parents about pneumonia. The parents who have children with concomitant diseases should be more aware to prevent their children from pneumonia. The department of medical records must complete the card status registration especially in history of birth weight and exclusive breastfeeding.Keywords: Describe, Children under three years and Pneumonia